Kelekatan Modal Sosial Pada Keluarga Santri Di Pulau Madura - Farahdilla Kutsiyah; Lukmanul Hakim; Ummu Kalsum (Palita: Journal of Social Religion Research, 2020)
AbstractA large capital owned by Pesantren (Islamic boarding schools) is the Ahlus sunnah waljamaah values which are juxtaposed with local wisdom. Madura Island is known as the island of a thousand Pesantren. Its existence affects the social structure and interaction of people on the island of Madura, where the resources embedded on them are called social capital. This study uses the librarian research and personal observation at several location points in Madura Island. The results showed that the attachment of Pesantren's social capital on santri families in Madura Island was the norm namely obedience to Kiai (religious leaders of Islamic boarding schools), barokah (divine blessing), high solidarity among fellow santri and simplicity. Networks such as recitation (koloman), alumnus ties, Istighozah (praying together for proposing forgiveness and hope), togetherness "ala pondok pesantren” (pesantren style)" and Imtihan (contest at the end of an academic year). Trust is honest and convinced behaviour as well as a belief of santri families towards pesantren. AbstrakModal besar yang dimiliki pesantren adalah nilai-nilai Ahlus sunnah waljamaah (Aswaja) yang disandingkan dengan kearifan lokal. Pulau Madura dikenal sebagai Pulau seribu pesantren. Keberadaannya berdampak terhadap struktur dan interaksi sosial masyarakat di Pulau Madura, dimana didalamnya terlekat modal sosial. Penelitian ini  menggunakan penelusuran kepustakaan dan observasi personal pada beberapa titik lokasi di Pulau Madura. Hasil penelitian menunjukkan bahwa kelekatan modal sosial pesantren pada keluarga santri di Pulau Madura adalah norma yakni kepatuhan terhadap Kiai, barokah, solidaritas tinggi antar sesama santri dan kesederhanaan, Jaringan seperti pengajian (koloman), ikatan alumni, Istighozah, kebersamaan ”ala pondok” dan Imtihan, kepercayaan yakni perilaku jujur & amanah serta kepercayaan keluarga santri terhadap pesantren.